2021
DOI: 10.1186/s40659-021-00348-0
|View full text |Cite
|
Sign up to set email alerts
|

Electroacupuncture suppresses glucose metabolism and GLUT-3 expression in medial prefrontal cortical in rats with neuropathic pain

Abstract: Background Accumulating evidence has demonstrated that the electroacupuncture (EA) stimulation could effectively alleviate neuropathic pain. The medial prefrontal cortex (mPFC) is a vital part of the cortical representation of pain in the brain, and its glucose metabolism is mostly affected in the progression of pain. However, the central mechanism of EA analgesia remains unclear. Methods Fifty-four male SD rats were equally randomized into sham su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 48 publications
0
14
0
1
Order By: Relevance
“…In the PCPA+7,8-DHF group (n = 10), the TrkB agonist 7,8-DHF was injected intraperitoneally at a concentration of 10 mg/ml on day 2 after the model was established. In the PCPA + DHS+7,8-DHF group (n = 10), the TrkB agonist 7,8-DHF was injected intraperitoneally at a concentration of 10 mg/ml on day 2 after the model was established, and needling was performed 6 h later (same procedure as in the PCPA + DHS group) once per day for 5 days [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…In the PCPA+7,8-DHF group (n = 10), the TrkB agonist 7,8-DHF was injected intraperitoneally at a concentration of 10 mg/ml on day 2 after the model was established. In the PCPA + DHS+7,8-DHF group (n = 10), the TrkB agonist 7,8-DHF was injected intraperitoneally at a concentration of 10 mg/ml on day 2 after the model was established, and needling was performed 6 h later (same procedure as in the PCPA + DHS group) once per day for 5 days [ 18 ].…”
Section: Methodsmentioning
confidence: 99%
“…Recently it has been revealed that the analgesic effect of acupuncture for NP may be related to metabolic regulation. EA at GB30 and GB34 significantly reversed increase in glucose metabolism induced by CCI and decreased the protein expression of glucose transporter 3 (GLUT-3) in the left medial Prefrontal Cortex (mPFC), suggesting that the analgesic effect of EA may be related to the inhibition of glucose metabolism and GLUT-3 expression in the mPFC ( 12 ). In a study involving the BPAI model, the brain metabolic connections between the bilateral hemisphere: somatosensory cortex (SC), the motor cortex (MC), caudate putamen (Cpu), and dorsolateral thalamus (DLT) were decreased compared with the normal animals.…”
Section: Mechanism Of Action Of Acupuncture In the Treatment Of Neuro...mentioning
confidence: 99%
“…A variety of neuropathic pain animal models which induced by central or peripheral nerve injury have been used to study the acupuncture mechanism ( Table 3 ; Zhang Y. et al, 2018 ; Li et al, 2019b ; Huo B.B. et al, 2020 ; Du et al, 2021 ; Jang et al, 2021 ; Jiang et al, 2021 ; Wei et al, 2021 ; Xu et al, 2021 ; Zou et al, 2021 ). In addition to animal models of nerve ligation, there are injectable chemotherapy drug-induced neuropathy, post-herpetic neuralgia, and diabetes-induced peripheral nerve injury ( Colleoni and Sacerdote, 2010 ).…”
Section: Animal Models Of Neuropathic Painmentioning
confidence: 99%